ABSTRACT NOUNS AND THEIR STUDY IN UZBEK LINGUISTICS (Scientific journal of the Fergana State University, 2023)
This article covers the concept of abstraction and its relation to human thinking. When explaining the concept of abstraction, reference is made to myths, examples of folklore, and religious texts. The article explains the grammatical features of abstract and concrete nouns. The history of Uzbek language grammar and the research conducted in this field will be discussed. Avesta, the holy book of Zoroastrian religion, examples of folk oral creativity and abstract nouns found in Alisher Navoi's work will be discussed. Denotative and significant meanings are explained. The organization of abstract nouns in Uzbek linguistics and the research conducted in this field are discussed.